Дослідження методу корекції звука для компенсації впливу приміщення - Древальський, Р. В. (ХНУРЕ, 2021)
This paper investigates the method of compensation of the room acoustic characteristics. Compensation is performed by the method of complex frequency response equalization. The equalizer frequency response is inverse to the room frequency response. To determine the latter, preliminary sweep-tone measurements are used. The possibilities of the system of through equalization are experimentally investigated, the limitations of its use are determined. The equalization system allowed to reduce the non-uniformity of the frequency response from 10 to 3 dB.
Keywords: звук; корекція